Carbon-Coated Magnetic Nanoparticle Dedicated to MRI/Photoacoustic Imaging of Tumor in Living Mice - Li, Yujing; Ye, Fei; Zhang, Shanxiang; Ni, Wenjun; Wen, Liewei; Qin, Huan (Frontiers in Bioengineering and Biotechnology, 2021)
Multimodality imaging can reveal complementary anatomic and functional information as they exploit different contrast mechanisms, which has broad clinical applications and promises to improve the accuracy of tumor diagnosis. Accordingly, to attain the particular goal, it is critical to exploit multimodal contrast agents. In the present work, we develop novel cobalt core/carbon shell–based nanoparticles (Cobalt at carbon NPs) with both magnetization and light absorption properties for dual-modality magnetic resonance imaging (MRI) and photoacoustic imaging (PAI). The nanoparticle consists of ferromagnetic cobalt particles coated with carbon for biocompatibility and optical absorption. In addition, the prepared Cobalt at carbon NPs are characterized by transmission electron microscope (TEM), visible–near-infrared spectra, Raman spectrum, and X-ray powder diffraction for structural analysis. Experiments verify that Cobalt at carbon NPs have been successfully constructed and the designed Cobalt at carbon NPs can be detected by both MRI and PAI in vitro and in vivo. Importantly, intravenous injection of Cobalt at carbon NPs into glioblastoma-bearing mice led to accumulation and retention of Cobalt at carbon NPs in the tumors. Using such a multifunctional probe, MRI can screen rapidly to identify potential lesion locations, whereas PAI can provide high-resolution morphological structure and quantitative information of the tumor. The Cobalt at carbon NPs are likely to become a promising candidate for dual-modality MRI/PAI of the tumor.